Identification of peptidic substrates for the human kinase Myt1 using peptide microarrays. Issue 15 (1st August 2015) - Rohe, Alexander; Platzer, Charlott; Masch, Antonia; Greiner, Sandra; Henze, Claudia; Ihling, Christian; Erdmann, Frank; Schutkowski, Mike; Sippl, Wolfgang; Schmidt, Matthias
Graphical abstract: Abstract: Myt1 kinase is a member of the Wee-kinase family involved in G2/M checkpoint regulation of the cell cycle. So far, no peptide substrate suitable for activity-based screening has been reported, hampering systematic development of Myt1 kinase inhibitors. Myt1 inhibitors had to be identified by using either binding assays or activity assays with expensive proteinous substrates. Here, a peptide microarray approach was used to identify peptidic Myt1 substrates. Wee1 kinase was profiled for comparison using the same technology. Myt1 hits from peptide microarray experiments were verified in solution by a fluorescence polarization assay and several peptide substrates derived from cellular proteins were identified. Subsequently, phosphorylation site determination was carried out by MS fragmentation studies and identified substrates were validated by kinase inhibitor profiling.